THE CORRELATION BETWEEN SELF-CONCEPT AND COLLAGE STUDENTS' SPEAKING SKILL - Sri Ananda Pertiwi (PT Akselerasi Karya Mandiri, 2023)
This study investigates the correlation between students' self-concept and their English-speaking skills. This study is correlational research. Thirty-two students majoring in the English education department at a university were involved as the samples in this study. Spoken tests were used to collect data on students' speaking skills, and questionnaires to collect data on students' self-concept. Spearman rank analysis is used to test the data. Based on the results of the correlation analysis between students' self-concept and students' English-speaking skills. The data shows that the sig. (2tailed) 0.012 < 0.05, which means there is a correlation between students' self-concept and their English-speaking abilities. A correlation coefficient score shows 0.440, which is classified as a